The kinetoplastid-infecting Bodo saltans virus (BsV), a window into the most abundant giant viruses in the sea - Deeg, Christoph M; Chow, Cheryl-Emiliane T; Suttle, Curtis A (eLife, 2018)
Giant viruses are ecologically important players in aquatic ecosystems that have challenged concepts of what constitutes a virus. Herein, we present the giant Bodo saltans virus (BsV), the first characterized representative of the most abundant group of giant viruses in ocean metagenomes, and the first isolate of a klosneuvirus, a subgroup of the Mimiviridae proposed from metagenomic data. BsV infects an ecologically important microzooplankton, the kinetoplastid Bodo saltans. Its 1.39 Mb genome encodes 1227 predicted ORFs, including a complex replication machinery. Yet, much of its translational apparatus has been lost, including all tRNAs. Essential genes are invaded by homing endonuclease-encoding self-splicing introns that may defend against competing viruses. Putative anti-host factors show extensive gene duplication via a genomic accordion indicating an ongoing evolutionary arms race and highlighting the rapid evolution and genomic plasticity that has led to genome gigantism and the enigma that is giant viruses. In oceans, rivers and lakes, there are about a million viruses in every milliliter of water. Most of these viruses are tiny, often 10 or 100 times smaller than bacteria. However, a few reach a similar size and complexity to bacteria, and so stand out as relative giants. Relative to other viruses, Giant Viruses have much more DNA in their genome, which in turn provides the genetic template to produce the proteins that allow viruses to reproduce largely independently of its host. Typically, more than half of the genes encoded by Giant Viruses have no evident similarity to genes from other viruses or cellular life. Sequencing DNA from ocean water suggests that Giant Viruses are abundant and ecologically important; yet, few have been isolated from the microbes that they infect. Without being able to study Giant Viruses in the laboratory, little can be known about their biology, the way they infect their hosts, and their broader influence on aquatic life. Deeg et al. have now isolated and characterized the giant Bodo saltans virus (BsV), a Giant Virus that infects an ecologically important microbe commonly found in aquatic environments. Sequencing the genome of BsV revealed many previously unknown genes, as well as several unusual features. For example, the genome contains movable genetic elements that might help to fend off other giant viruses by cutting their genomes. In addition, the set of genes used by BsV to translate mRNA templates into proteins differs from those found in other giant viruses, implying that they are not derived from a more complex common ancestor. The size of the genome appears to have grown rapidly by the duplication of genes at the end of the genome – a feature known as a genomic accordion. The identity of the duplicated genes suggests that there is an evolutionary arms race with its host that forces genome expansion. Further studies of the BsV genome could help researchers to understand the origin of gigantism in the genomes of giant viruses.